Higher‐order structure formation using refined monomer structures of lipid raft markers, Stomatin, Prohibitin, Flotillin, and HflK/C‐related proteins - Hideshi Yokoyama; Ikuo Matsui (FEBS Open Bio, 2023)
Currently, information on the higher‐order structure of Stomatin, Prohibitin, Flotillin, and HflK/C (SPFH)‐domain proteins is limited. Briefly, the coordinate information (Refined PH1511.pdb) of the stomatin ortholog, PH1511 monomer, was obtained using the artificial intelligence, ColabFold: AlphaFold2. Thereafter, the 24mer homo‐oligomer structure of PH1511 was constructed using the superposing method, with HflK/C and FtsH (KCF complex) as templates. The 9mer‐12mer homo‐oligomer structures of PH1511 were also constructed using the ab initio docking method, with the GalaxyHomomer server for artificiality elimination. The features and functional validity of the higher‐order structures were discussed. The coordinate information (Refined PH1510.pdb) of the membrane protease PH1510 monomer, which specifically cleaves the C‐terminal hydrophobic region of PH1511, was obtained. Thereafter, the PH1510 12mer structure was constructed by superposing 12 molecules of the Refined PH1510.pdb monomer onto a 1510‐C prism‐like 12mer structure formed along the crystallographic threefold helical axis. The 12mer PH1510 (prism) structure revealed the spatial arrangement of membrane‐spanning regions between the 1510‐N and 1510‐C domains within the membrane tube complex. Based on these refined 3D homo‐oligomeric structures, the substrate recognition mechanism of the membrane protease was investigated. These refined 3D homo‐oligomer structures are provided via PDB files as Supplementary data and can be used for further reference.